PEMANFAATAN EKSTRAK DAUN SIRSAK (Annona muricata L) SEBAGAI BAHAN PENGAWET KAYU ALAMI - Selvi Carolina; Wiwin Tyas Istikowati; Sunardi Sunardi (Universitas Lambung Mangkurat, 2020)
Wood fruits are susceptible to harmful organisms, as most have low durability classes. The purpose of this research is to measure the absorption, leaf extract retention, percentage of weight reduction, degree of damage, and mortality of termites in rambutan wood preservation by cold bath method. And know the durability of rambutan wood (N. Lappaceum L) preserved with soursop leaf extract preservative against ground termite attack. The result of this research is the highest average absorption value at 200 g/l concentration with 7 days immersion time of 0.976 g/cm3 . the highest average actual retention rate of 0.030 g/cm3 at a concentration of 200 g/l with a 7-day immersion period and the higher concentration and the longer immersion period the higher of absorption and actual retention value. The effect of soaking time and the concentrarion level of soursop leaf extract on the soil termite infestation is the duration of immersion affect the level of wood durability the higher the concentration of preservative and soaking time, the higher the durability of rambutan wood 7 days with a concentration of 200 grams.Keywords: Soursop leaf extract; wood preservation; rambutan wood